Untangling wicked problems. Issue 2 (18th April 2016) - McCALL, Raymond; Burge, Janet
Abstract: More than 40 years after Rittel and Webber published the first articles on the theory of wicked problems this theory has been applied to a wide range of fields involved in real-world problem solving. Interest in the theory seems greater than ever. This has led to an interest in rethinking the theory. A number of authors do this by imposing interpretations on the theory that are incompatible with each other and with the statements of the theory's authors. We agree that it is time to critically reexamine the theory and rethink what implications it has for design. However, rather than imposing an incompatible interpretation, our approach is see what new conclusions can be drawn from a systematic and critical examination of what Rittel and Webber actually said. This reexamination of their specific claims and arguments is what we call untangling wicked problems . From this untangling, we derive new conclusions about how designers should tackle wicked problems and how design rationale can aid them in doing so.